2009
DOI: 10.1016/j.msea.2008.10.039
|View full text |Cite
|
Sign up to set email alerts
|

High cycle fatigue behaviour of Ti–6Al–4V fabricated by metal injection moulding technology

Abstract: Titanium alloys exhibit an excellent combination of properties, including high specific strength and excellent bio-compatibility. Recently, parts made from titanium alloys such as Ti-6Al-4V have been manufactured by metal injection moulding (MIM) and exhibited excellent tensile properties (UTS > 800 MPa and 15%). However to date, few information concerning the fatigue properties of such material has been presented in the literature. Thus, in the present study, the influence on the high cycle four point ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 12 publications
3
49
1
Order By: Relevance
“…[13] It is also much lower than the endurance limit of %800 MPa obtained for the thermo-mechanically treated Ti-6Al-4V alloy with an equiaxed microstructure. [14] However, other recent investigations have shown that it is possible to increase the fatigue resistance of Ti-6Al-4V components produced by MIM technology by changing the surface quality [15] or by controlling specific processing parameters such as binder content [16] and powder particle size. [11] Nevertheless, better fatigue resistance is still desirable for MIM parts.…”
Section: Introductionmentioning
confidence: 99%
“…[13] It is also much lower than the endurance limit of %800 MPa obtained for the thermo-mechanically treated Ti-6Al-4V alloy with an equiaxed microstructure. [14] However, other recent investigations have shown that it is possible to increase the fatigue resistance of Ti-6Al-4V components produced by MIM technology by changing the surface quality [15] or by controlling specific processing parameters such as binder content [16] and powder particle size. [11] Nevertheless, better fatigue resistance is still desirable for MIM parts.…”
Section: Introductionmentioning
confidence: 99%
“…The static mechanical properties of injection molded titanium alloy compacts have been reported so far [19][20][21]; however, there are few reports regarding the dynamic fracture characteristics [22,23]. As the dynamic fatigue behavior is of great importance in practical use, fatigue characteristics of injection molded Ti alloy compacts are reviewed.…”
Section: Fatigue Properties Of Ti Alloys Fabricated By Mimmentioning
confidence: 99%
“…Implants that function as bones, such as artificial joint endoprostheses, hip joints, bone plates, and tooth roots, are used under severe oscillating loading conditions and some of them are usually subjected to long-term cyclic loading [18]. It is reported that fatigue fracture is the most part of mechanical failure of titanium alloy implants [18][19][20]. Therefore, the long life fatigue properties of titanium alloys should be investigated to adjust the design.…”
Section: Introductionmentioning
confidence: 99%